algebra

posted by .

solve for the variable in the equation 3(-2 - 3x) = -9x - 4

  • algebra -

    3(-2 - 3x) = -9x - 4

    -6 + 9x = -9x - 4

    Can't be solved.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Algebra22222!!!

    Choose the ordered pair that is a solution to the system of equations. 3x - y = 10 -x + y = -4 (3, -7) (-1, 3) (3, -1) (3, 1) Follow the example I gave in your previous question. I'm not going to do all of them. You want to eliminate …
  2. math, algebra

    How do I solve for the following: Directions solve each literal equation for the individual variable. 2x + 3y -6 (for x ) Linear equation It has to equal something. What you have is a statement, not an equation.
  3. algebra

    solve each literal equation for the indicated variable linear equation for x 2x+3y=6 can some one give me a example and show me how the steps go to solve this problem please Subtract 3y from both sides of the equation, and then divide …
  4. Algebra

    I'm not sure if I have this correct I have to solve each literal equation for the indicated variable. A=1/2h(B+b)variable is (b). I have the answer as: 2A=h(B1+b2) 2A/h=B1+b2 (2A/h)-b2=B1 Is this correct?
  5. math solutions

    solve the equation abx=cy for each of following the variable x the variable a the variable c solve the equation ay/x the variable y the variable z the variable x solve each of following for variable y 3y=ab ab=cy ayc=bx bx/y=R zy/x=b
  6. math (this correct)

    What is the difference between an equation and an expression?
  7. Math

    What is the difference between an equation and an expression?
  8. Algebra

    What is the difference between and equation and an expression?
  9. algebra

    What is the difference between an equation and an expression?
  10. Algebra

    There are 4 problems that I don't understand how to solve so, please help me. A numerical explanation with words explanation would be nice. Thank you tutors. Rewrite each equation so it is in the form ax + b = c or x + d/e = f, where …

More Similar Questions